Environmental Jurisprudence (Fiqh al-Bi'ah) and the Urgency of Natural Resource Conservation from an Islamic Legal Perspective - Nurul Hidayah (Samarinda International Journal of Islamic Studies (SIJIS), 2025)
This paper explores the intersection of Islamic legal principles, specifically Fiqh al-Bi'ah (environmental jurisprudence), and the pressing need for natural resource conservation. It examines the foundational texts of Islam to derive ethical and legal frameworks for environmental stewardship. The study investigates how Islamic teachings can inform and guide sustainable practices, offering a unique perspective on environmental challenges. The research highlights the potential of Fiqh al-Bi'ah to provide a comprehensive approach to environmental protection, integrating religious values with practical solutions for resource management and conservation. By analyzing relevant Islamic texts and contemporary environmental issues, this paper underscores the urgency of incorporating Islamic principles into environmental policies and practices to foster a more sustainable and just future.